Kalak Kampong: Identitas dari Kesadaran Kelas dan Inferioritas di Aceh Singkil-Subulussalam: Kalak Kampong: An Identity Rooted in Class Consciousness and Inferiority in Aceh Singkil-Subulussalam - Pohan, Zulfikar Riza Hariz (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The term ‘kalak kampong’ (villagers) in Singkel (Aceh Singkil-Subulussalam) is commonly used by residents of riverbanks (julu) or hillsides (deleng). On one hand, this term is often interpreted as a hesitation to express their ethnic identity. The accusation of ‘cultural hesitation’ generally comes from local political elites in Singkel who have formed the ethnic concept known as the Singkil Tribe. In fact, the terminology ‘kalak kampong’ is an explanation of the power and economic disparities occurring in Singkel due to the persistence of modernism and developmentalism in the Aceh community. ‘Kalak kampong’ signifies that they feel inferior and not on the same social level as ‘urban people’ or communities that use the Indonesian language (urban language/Bahasa Indonesia). On the other hand, the term ‘kalak kampong’ also represents a unifying identity in Singkel, namely the unity as a traditional community that is homogeneous and industrially lagging behind modernization. This research was conducted using a descriptive analysis approach in cultural studies, with data collected through field observations and literature analysis related to ethnic identity and socio-economic dynamics in Singkel. The research aims to examine the relationship between power and economic disparities and the perception of ‘kalak kampong’ within the Aceh community. The results show that local political elites play a significant role in shaping and reinforcing the ethnic concept of the ‘Suku Singkil’ for their political and social. [Penyebutan ‘kalak kampong’ (Orang kampung) di Singkel (Aceh Singkil-Subulussalam) lazimnya digunakan oleh penduduk pinggiran sungai (julu) atau perbukitan (deleng). Di satu sisi, sebutan tersebut sering ditafsirkan sebagai kegagapan untuk menyatakan identitas kesukuan mereka. Tuduhan ‘gagap kebudayaan’ tersebut umumnya berasal dari elite-elite politik lokal di Singkel yang membentuk konsep etnis yang disebut sebagai Suku Singkil. Padahal, terminologi ‘kalak kampong’ merupakan sebuah penjelasan ketimpangan relasi kuasa dan ekonomi yang terjadi di Singkel atas langgengnya modernisme dan pembangunanisme komunitas Aceh. ‘Kalak kampong’ adalah sebutan bahwa mereka merasa lebih rendah dan tak sekelas pergaulannya dengan ‘orang kota’ atau komunitas yang menggunakan bahasa Indonesia (bahasa kota). Di sisi yang lain, penyebutan ‘kalak kampong’ juga merupakan identitas persatuan di Singkel. Penelitian ini berlangsung melalui pendekatan analisis deskriptif pada studi budaya (cultural studies), data dikumpulkan melalui observasi lapangan serta analisis literatur terkait identitas kesukuan dan dinamika sosial-ekonomi di Singkel. Penelitian ini bertujuan untuk meneliti hubungan antara ketimpangan relasi kuasa dan ekonomi dengan persepsi 'kalak kampong' dalam komunitas Aceh. Hasilnya menunjukkan bahwa elite politik lokal memainkan peran signifikan dalam membentuk dan memperkuat konsep etnis ‘Suku Singkil’ untuk kepentingan politik dan sosial mereka]. Kata kunci: Aceh, Inferior, Singkel, Suku Singkil, Kelas Sosial, Modernisasi.